The Twofold Nature of Spontaneous Actions: Insights from Practice Turn in Management - Patora-Wysocka, Zofia (Studia Oeconomica Posnaniensia, 2016)
The aim of the article is to explore the twofold nature of spontaneous actions in management. The thesis posits that spontaneity is an important category initiating changes in an enterprise in the course of reproduced practices. Research methods included an in-depth interview and non-participatory observations. The issue of spontaneity can be perceived through the aspect of daily routines as well as from the opportunistic perspective. Business practices constitute some institutional schemas that are recreated on a daily basis. The kind of institution determines the way entrepreneurs cope with the shifting logics of everyday business life. Therefore they recreate practices spontaneously and not in a discursive manner. On the other hand spontaneous actions may imply grasping opportunities. This is particularly important when an organisation operates in a turbulent market. The findings confirm the dual character of spontaneous activities in the everyday practice of enterprises. Unplanned processes may integrate and strengthen routines that are very important elements of "emerging" perpetuation in an enterprise. They are stimuli to innovation and the adoption of new practices. This processual perspective referring to management practices offers a new framework for an analysis of change and entrepreneurial practice in management.